Dietary energy and protein gradients drive metabolic adaptation in growing-finishing yaks on the Qinghai-Tibet plateau - Shoupei Zhao; Jia Zhou; Shengtao Guan; Xiaolin Wang; Xiao Wen; Kaiqiang Zhao; Huaming Yang; Lianghao Lu; Bao Zhang; Yuanyuan Chen; Quanhui Peng; Lizhi Wang; et al. (Animal Nutrition)
The study investigated the metabolic responses of yaks to dietary net energy for gain (NEg) and metabolizable protein (MP), and explored potential biomarkers for average daily gain (ADG) in serum metabolites. A total of 40 three-year-old yaks (initial body weight = 255 ± 8.04 kg) were assigned to a 2 × 2 factorial treatment arrangement based on dietary NEg (4.18 vs 4.81 MJ/kg DM; low NEg [LE] vs high NEg [HE]) and MP (72.0 vs 82.8 g/kg DM; low MP [LP] vs high MP [HP]), comprising 4 treatments with 10 replicates each (1 yak per replicate). The yaks were fed these diets for 55 days including a 15-day adaptation period. Yaks on HP diets had greater ADG (P = 0.013) and a reduced feed-to-gain ratio (P = 0.019) compared to those on the LP diet, and those on the LE diet had greater dry matter intake (P < 0.001) but unaffected ADG compared to those on the HE diet (P > 0.05). Dietary NEg interacted with MP in relation to the apparent digestibility of dry matter (P = 0.028) and crude protein (P < 0.001). The apparent digestibility of gross energy (GE), organic matter, and neutral detergent fiber in yaks on the HE diet was greater than those in yaks on the LE diet (P < 0.05). The digestibility of GE in yaks on the HP diet was lower than those on the LP diet (P = 0.011). An significant interaction between dietary NEg level and MP level was observed on serum total bilirubin concentration, catalase concentration, and superoxide dismutase concentration (P < 0.05). Yaks fed HE diets exhibited higher serum glutathione peroxidase protein concentration (P < 0.001), but lower serum triglyceride concentration (P = 0.012) compared to those fed LE diets. Serum level of alanine transaminase was higher in yaks on the HP diet compared to those on the LP diet (P = 0.038). Untargeted metabolomics identified novel biomarkers linked to dietary NEg and MP levels, revealing that the HE diet enhanced adenosine triphosphate production through acetyl-CoA synthesis and affected amino acid, fat, and carbohydrate pathways (P < 0.05). The HP diet altered the synthesis of aromatic amino acids and vitamins (P < 0.05). Additionally, random forest analysis identified N-(9-oxodecyl) acetamide and biliverdin, as biomarkers for predicting ADG. These findings provide a theoretical foundation for the effective feeding and nutritional management of yaks.